Regulation and characterization of protein products coded by the nif (nitrogen fixation) genes of Klebsiella pneumoniae. - Roberts, G P (1978)
Two hundred and thirty-five Nif- strains of Klebsiella pneumoniae were characterized by two-dimensional polyacrylamide gel electrophoresis. Forty-two of these strains were tested further by in vitro acetylene reduction assays. By these techniques, nine nif-coded polypeptides were identified, and eight of these were assigned to specific nif genes. Nitrogenase component I required nifK and nifD, which coded for the beta and alpha subunits, and nifB, -E, and -N were required for the iron-molybdenum cofactor, which is a part of the active site of nitrogenase. nifH coded for the structural protein of component II, and nifM and nifS products seemed to be necessary for the synthesis of an active component II. There were two genes, nifF and nifJ, that were required for N2 fixation in vivo but not for N2 fixation in vitro. There were at least two cases (nifE and nifN, nifK and nifD) of two proteins that seemed to require each other for stability in vivo. Regulation of N2 fixation is apparently complex, and this is reflected by the assignment of regulatory functions to the gene products of nifA, nifL, nifK, nifD, nifH, and NIFJ.